ANALISIS KESEIMBANGAN JANGKA PENDEK DAN JANGKA PANJANG KONSUMSI ENERGI DI INDONESIA - Ilmanita Ilmanita; Hasdi Aimon (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
The study aims to explained the balance of short term and long term energy comsumption in Indonesia. The data used time series from 1978 to 2017. The method analysis used the Simultaneous Equation Model and Error Correction Model (ECM). The results of the study show that the long term oil production, national income and import of oil have significant positive effect to energy consumption in Indonesia. Oil price have significant negative effect to energy consumption. In the short term oil production, national income and import of oil have significant positive effect to energy comsumption in Indonesia. Oil price have significant effect to energy comsumption in Indonesia. In the long term national income have significant positif effect to import of oil in Indonesia, oil price and energy comsumption have significant positive effect to import of oil in Indonesia and exchange rate does not have significant effect to import of oil in Indonesia. In the short term national income, exchange rate and energy consumption does not have significant effect to import of oil in Indonesia, oil price have significant positive effect to import of oil in Indonesia.